PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATA PELAJARAN MATEMATIKA SISWA KELAS III SEKOLAH DASAR NEGERI 03 POLOKARTO KECAMATAN POLOKARTO KABUPATEN SUKOHARJO TAHUN AJARAN 2024/2025 - Nesya Fitria Rahmadhani; Moefty Mahendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Lack of activity and learning outcomes in mathematics is due to the learning model applied being less effective, causing students to be less interested in participating in learning. The purpose of this study was to improve the activity and learning outcomes of grade III students in mathematics subjects at SD Negeri 03 Polokarto Sukoharjo. The type of research used was Classroom Action Research (CAR) consisting of 2 cycles. The research subjects were 23 students consisting of 13 male students and 10 female students. Data collection techniques in this study used observation, documentation, tests, and questionnaires. The instruments used were student observation sheets, teacher observation sheets, test questions, and questionnaires. The indicators of success are the success of student learning activity through a questionnaire of 75% and the indicator of student learning outcomes through a test of 75% of students who meet the KKM 70. The results of the study can show that the Application of the Snowball Throwing Learning Model to Improve the Activity and Learning Outcomes of the Remaining Mathematics Subject of Class III of Elementary School 03 Polokarto, Polokarto District, Sukoharjo Regency, Academic Year 2024/2025 can be concluded that it can increase student learning activity in mathematics subjects of class III by 47.46% in the pre-cycle, in cycle I it increased by 69.85% and increased again in cycle II by 82.39%. The application of the Snowball Throwing learning model can also improve student learning outcomes in mathematics subjects of class III with results of 30.43% in the pre-cycle, in cycle I it increased by 65.22% and increased in cycle II by 86.96%.